Perinatal exposure to 2, 2′, 4′4′ −Tetrabromodiphenyl ether induces testicular toxicity in adult rats. (15th August 2017) - Khalil, Ahmed; Parker, Mikhail; Brown, Sarah E.; Cevik, Sebnem E.; Guo, Lian W.; Jensen, Jake; Olmsted, Alexandra; Portman, Daneal; Wu, Haotian; Suvorov, Alexander
Abstract: Since 1965, polybrominated diphenyl ethers (PBDEs) have been used internationally as flame-retardant additives. PBDEs were recently withdrawn from commerce in North America and Europe due to their environmental persistence, bioaccumulative properties and endocrine-disrupting effects. Generations exposed perinatally to the highest environmental doses of PBDE account for one-fifth of the total United States population. While, toxicity of PBDE for the male reproductive system has been demonstrated in several human and animal studies, the long-lasting effects of perinatal exposures on male reproduction are still poorly understood. In this study, pregnant Wistar rats were exposed to 0.2 mg/kg 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) from gestation day 8 until postnatal day 21. Male reproductive outcomes were analyzed on postnatal day 120 in offspring. Exposed animals had significantly smaller testes, displayed decreased sperm production per testis weight, had significantly increased percentage of morphologically abnormal spermatozoa, and showed an increase in spermatozoa head size. Perinatal BDE-47 exposure led to significant changes in testes transcriptome, including suppression of genes essential for spermatogenesis and activation of immune response genes. In particular, we observed a 4-fold average decrease in expression of protamine and transition protein genes in testes, suggesting that histone-protamine exchange may be dysregulated during spermatogenesis, resulting in an aberrant sperm epigenome. The possibility of long-lasting effects of developmental PBDE exposures calls for additional studies to build a foundation for the development of preventive and protective interventions against the environmentally-induced decline in fertility.